Implantable cardioverter defibrillators in adult congenital heart disease: long-term follow up of therapies, complications and clinical events. (24th May 2021) - Ferreira, V; Cruz Coutinho, M; Portugal, G; Silva Cunha, P; Valente, B; Laranjo, S; Branco Mano, T; Castelo, A; Garcia Bras, P; Cardoso, I; Bras, M; Sousa, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Adults with congenital heart disease (ACHD) at increased risk for sudden cardiac death (SCD) often undergo implantable cardioverter defibrillator (ICD) implantation at young ages. Data evaluating the long-term outcomes of ICD in this population remain scarce. We aimed to characterize the population with ACHD and an ICD. Methods: Consecutive ACHD submitted to an ICD implantation in a single tertiary center were evaluated. Data on baseline clinical features, heart defect, indication for ICD, type of device, ICD-related complication and therapies and mortality during follow-up were collected. Results: A total of 34 patients (P) were evaluated. Median age at implant was 39.3 years (interquartile range [IQR] 29-5-53.6) and median left ventricular ejection fraction (LVEF) was 43.5% (IQR 28.0-53.3). The most common heart defect was tetralogy of Fallot (11P;32, 3%), followed by dextro-transposition of the great arteries, ostium secundum atrial septal defect (ASD) and ventricular septal defect (Figure 1). All P were submitted to surgical correction (median age at surgery 12.5 years [IQR 3.0-29.1]). Sixteen P underwent ICD implantation for primary prevention of SCD, owing to complex cardiopathy and ventricular dysfunction, and 18P due to spontaneous ventricular tachyarrhythmias. The implantable devices were a single-chamber ICD in 55.9%, a double-chamber ICD in 17.6%, a subcutaneous ICD in 20.6% and a CRT-D in 5.9%. During a median follow-up of 4.5 years (IQR 2.1-8.8), 52.9% of the P received appropriate ICD therapies, corresponding to 37.5% and 66.7% of primary and secondary prevention P, respectively. Median time to first arrhythmic event was 25.3 months (IQR 13.7-52.9). Six P (17.6%) suffered ICD-related complications and 20.6% received inappropriate therapies due to supraventricular tachyarrhythmias. During follow-up, 8.8% were submitted to heart transplant and 29.4% died (Table 1).  ICD therapies were associated with a composite of death, cardiac transplantation and hospital admission (OR 5.0, 95% CI 1.0-24.3). Conclusion: ACHD with ICD experience high rate of appropriate therapies, including those implanted for primary prevention. The long-term burden of ICD-related complications and inappropriate shocks underlines the need for careful risk stratification and close monitoring. The increased survival of this population justifies collecting data on long-term outcomes to improve its care.